Phenotypic and molecular analyses of coagulase negative Staphylococci, predominantly comprising Staphylococcus epidermidis, isolated from a student population in Malaysia - Pung, Hui Ping (2015)
Coagulase negative staphylococci (CoNS), predominantly Staphylococcus epidermidis, are commonly considered as commensal skin and nasal colonizing bacteria but have emerged as one of the leading causes of nosocomial infections. To date, limited studies have been conducted to investigate CoNS or methicillin resistant CoNS (MR-CoNS) in Malaysian community. Hence, this study was initiated to evaluate the status of CoNS in relation to their nasal carriage, risk factors, antimicrobial resistance, molecular characteristics and genetic background of the bacterial collection in a student population. This study was conducted at Universiti Putra Malaysia in November 2013 involving 192 health science students. A self-administrated questionnaire on sociodemographic and risk factors was distributed, followed by collection of nasal swab. Cultivation on mannitol salt agar (MSA) plates and basic phenotypic tests were used to preliminarily differentiate CoNS from Staphylococcus aureus. All CoNS isolates were subjected to antibiotic susceptibility test against 10 antibiotics and mecA gene screening. The mecA positive isolates were further subjected to staphylococcal chromosome cassette mec (SCCmec) typing and multilocus sequence typing (MLST) to identify the SCCmec types and sequence type (ST) of the isolates, respectively. CoNS isolates that were resistant to at least one antibiotic or were mecA positive were subjected to species identification based on tuf gene sequencing, screening of erythromycin resistance associated genes (ermA, ermB, ermC, and msrA), random amplified polymorphic DNA- (RAPD) and enterobacterial repetitive intergenic consensuspolymerase chain reaction (ERIC-PCR). In this study, a total of 120 isolates of CoNS (62.5%) were collected from 192 health sciences students. Chi-square test showed significant association of nasal carriage of CoNS with gender (P = 0.0455), history of cold or fever (P = 0.0147) and presence of unhealed wound (P = 0.0467). Similarly, the P-value of the use of intravascular devices was close to significant (P = 0.0589). The other risk factors (ethnicity, health status and habit of touching nose) were deemed as statistically not significant. Resistance to penicillin was the highest among the isolates (58.3%) followed by tetracycline (9.2%), cefoxitin (8.3%), erythromycin (7.5%), oxacillin (6.7%), ceftazidime (5.0%), gentamicin (2.5%) and rifampin (1.7%). Two isolates of CoNS were identified as multidrug resistant strains (MDR) which are resistant to more than three antimicrobial families. Among 76 isolates that were subjected to tuf gene sequencing, 73 isolates were identified as S. epidermidis and three isolates as S. haemolyticus. Fifteen isolates of CoNS (12.5%) harbored mecA gene (13 S. epidermidis; 2 S. haemolyticus) whereas five isolates (4.2%) carried msrA gene (3 S. epidermidis; 2 S. haemolyticus). Twelve of the mecA positive isolates carried SCCmec type IV (11 S. epidermidis; 1 S. haemolyticus), two isolates carried SCCmec type II (1 S. epidermidis; 1 S. haemolyticus) and one isolate carried SCCmec type I (S. epidermidis). MLST analysis of MRSE isolates revealed four STs: ST57 (n=6), ST59 (n=1), ST72 (n=1) and ST193 (n=1). However, four of the isolates had non-typeable (new) ST. RAPD and ERIC analyses revealed that majority of the isolates were largely genetically distinct. We observed a potential dissemination of a few distinct MR-CoNS carrying predominantly SCCmec type IV in the population rather than a clonal spread in both analyses. Overall, the study showed a high prevalence of nasal carriage CoNS which had relatively low level of antibiotic resistance except for penicillin and had extensive genetic diversity.